1998
DOI: 10.1148/radiology.209.1.9769838
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary nodule detection: low-dose versus conventional CT.

Abstract: Low-dose CT is acceptable for pulmonary nodule identification, making it suitable for primary screening. These results confirm the strong effect of size, location, and angiocentricity on the sensitivity of nodule detection with conventional CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
1
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(71 citation statements)
references
References 0 publications
3
66
1
1
Order By: Relevance
“…The frequency and duration of follow-up is guided by consensus-based recommendations fi rst published by the Fleischner Society ( Fig 6 ) and subsequently endorsed in the second edition of these guidelines. 6,73 Decisions about the frequency and duration of follow-up for patients with small solid nodules need to weigh multiple considerations, including clinical risk factors; nodule size; the variable rate of nodule growth; the limited accuracy of available techniques for establishing growth by cross-sectional and volumetric measurements, especially for nodules that measure , 5 mm in size 81,83,130 ; concerns regarding radiation dose 24,131,132 ; risk factors for surgical complications; and cost. To date, recommendations from the Fleischner Society have not been subjected to formal validation, and limited data suggest that adherence may be suboptimal in some settings.…”
Section: 31mentioning
confidence: 99%
“…The frequency and duration of follow-up is guided by consensus-based recommendations fi rst published by the Fleischner Society ( Fig 6 ) and subsequently endorsed in the second edition of these guidelines. 6,73 Decisions about the frequency and duration of follow-up for patients with small solid nodules need to weigh multiple considerations, including clinical risk factors; nodule size; the variable rate of nodule growth; the limited accuracy of available techniques for establishing growth by cross-sectional and volumetric measurements, especially for nodules that measure , 5 mm in size 81,83,130 ; concerns regarding radiation dose 24,131,132 ; risk factors for surgical complications; and cost. To date, recommendations from the Fleischner Society have not been subjected to formal validation, and limited data suggest that adherence may be suboptimal in some settings.…”
Section: 31mentioning
confidence: 99%
“…Establishing such protocols often involves the use of phantoms due to the difficulty of employing patients when comparing different technical or procedural factors involving ionizing radiation [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Their work concerns pulmonary nodule detection, CT colonography, renal colic, acute appendicitis, chronic sinusitis and screening (Rusinek et al 1998;van Gelder et al 2002;Tack et al 2003aTack et al , 2003bKeyzer et al 2004). A recent study by Horger et al (2005) showed that whole-body low-dose MDCT is appropriate for the diagnosis of lytic bone changes and for the assessment of fracture risk in multiple myeloma patients -among whom it represents a serious alternative to current standards.…”
Section: Modalities For Dose Reduction In Musculoskeletal Ctmentioning
confidence: 99%